Calcium phosphate crystal forms in human jaw bones of changed osteoporotic structure - Poštić Srđan D. (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. Calcium phosphates are chemical compounds that can be found in various forms within nature, as well as in human jaws and bones. The aim of this study was to assess the structure of solid chemical compounds which form the structure of normal and osteoporotic jaw-bones. Materials and Methods. The jaw-bones taken from human cadavers were used in the study. Crystalographic forms of calcium phosphate, in the samples of human jaw-bone, were determined using X-ray diffraction technique. The experimental bone samples originated from osteoporotic jaw-bone of cadavers while control samples were taken from dentate jaw-bones of non-osteoporotic cadavers. Results. The results of this study showed that hydroxyapatite was the only phase determined in control non-osteoporotic bone samples. In experimental (osteoporotic) bone samples, the same phase was registered, as well as calcium monophosphate and hydrated calcium phosphate, registered as increments of values on α axis. Conclusion. Hydroxyapatite was the only compound detected in normal bone while osteoporotic bone contained others crystallographic forms of calcium phosphates.